“If You’re Male, You Get It More”: Experiences of Indonesian Female Academics Under New Managerialism - Siti Muflichah (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2024)
This study explores the career ladder experiences of female professors in Islamic higher education institutions in Indonesia. The experiences of Indonesian female academics are distinct compared to their counterparts worldwide, as they face unique challenges in attaining higher academic positions such as associate professor or professor. Female academics in Indonesia are often perceived as less productive in research and publication, hold fewer leadership roles, achieve lower academic ranks, and earn significantly less than their male peers. Employing a feminist research methodology, this study aims to amplify women’s voices and advocate for their advancement to higher positions. Through qualitative interviews and analysis using Miles and Huberman’s model, the study examines the lived experiences of female academics operating within the constraints of a new managerialism framework. The findings highlight a feminist perspective that is rarely acknowledged in the discourse on higher education in Indonesia. Drawing on Mohanty’s postcolonial feminist framework, the study celebrates the resilience and contributions of non-Western women while shedding light on the systemic barriers they face. Indonesian Muslim female academics report enduring gender bias, limited opportunities for leadership, and cultural norms that prioritize familial responsibilities over professional growth. These challenges restrict their potential and diminish their contributions to academia and research. This study serves as a critical call to address the structural inequities and cultural dynamics that hinder the progress of women in academia.